Travelling Waves of an n-Species Food Chain Model with Spatial Diffusion and Time Delays - Fei Hu; Yuyin Xu; Z. Wang; Wei Ding (Abstract and Applied Analysis, 2014)
We investigate an n-species food chain model with spatial diffusion and time delays. By using Schauder’s fixed point theorem, we obtain the result about the existence of the travelling wave solutions of the food chain model with reaction term satisfying the partial quasimonotonicity conditions.